The dosimetric evaluations for treatment planning on CE-pCT and VNC-pCT for ten breast cancer patients who underwent VMAT. - Jungye Kim (20485427) (2024)
Numbers in parentheses are standard deviations. CE-pCT, contrast enhanced planning computed tomography; HI, homogeneity index; PTV, planning target volume; VMAT, volumetric modulated arc therapy; VNC-pCT, virtual non-contrast planning computed tomography.